فقہ السیرۃ: ڈاکٹر محمد حمیداللہ کی اجتہادیفکر کا مطالعہ : Fiqh-Al-Sirah, A Study of Neologies Thought of Dr. Muhammad Hamidullah - ڈاکٹر محمد عبداللہ (Seerat Studies, 2024)
Dr. Muhammad Hamidullah (1908-2002) was a great Islamic Scholar of the twentieth century. The scope of his Contribution was spread over the Holy Quran, Hadith, Biography of the Prophet Muhammad (PBUH) and International Relations. More or less in each of above fields he composed numerous articles and writings, which comprise on huge collections of Books in different dialects.